2016
DOI: 10.1089/tmj.2015.0033
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Integrated Electronic Patient Portal in the Pediatric Population: A Systematic Review

Abstract: Reflecting the additional considerations of pediatric proxy access and fewer chronically ill patients, pediatric medicine has yet to use the patient portal as a modality for outcomes measurement. Given the paucity of studies within this age group, it is difficult to measure outcome improvements or the effect of patient record access on healthcare behaviors. This systematic review presents innovative research on the general acceptance of the patient portal among parents and highlights that the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…After removing duplicates and initial screening of titles and abstracts, 42 papers were retrieved for detailed evaluation. [24,25,26] which were part of another main study [6,27,28], leading to a total of 20 unique reviews [3,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The overall process of review selection was …”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates and initial screening of titles and abstracts, 42 papers were retrieved for detailed evaluation. [24,25,26] which were part of another main study [6,27,28], leading to a total of 20 unique reviews [3,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The overall process of review selection was …”
Section: Search Resultsmentioning
confidence: 99%
“…There were three reviews reporting positive effects of patient portals on better adherence to treatment and medication regimen [6,28,38]. However, overall evidence of improvement in quality of care was limited [6], and there was a lack of studies investigating long-term health outcomes [32]. As most of the patient portal evaluations targeted online interventions for chronic disease management (e.g.…”
Section: Narrative Synthesis Of the Evidence Of Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…A paucity of data exists to describe how portals are utilized by caregivers of pediatric patients. A 2015 systematic review of portals in the pediatric population identified only 11 relevant publications . Those studies assessed a range of issues including portal usage, usability, and value in transitioning care from a caregiver to teenager.…”
Section: Introductionmentioning
confidence: 99%